(untitled) (CIPEEX, 2024)
The purpose of this abstract was to present the importance of dendritic cells in the activation of the adaptive immune response. Dendritic cells (DC) are tissue phagocytes that act as the main antigen-presenting cells (APC) connecting the innate immune response with the adaptive immune response. CD have receptors that identify molecular patterns linked to diseasecausing agents and are able to capture, process, and present pathogens to lymphocytes. They process the aggressors into peptide fragments and display them on their plasma membrane associated with molecules of major histocompatibility complex (MHC) classes I and II. In B lymphocytes, this combination is called antigen, and in T lymphocytes, it is a peptide linked to MHC, which is vital for the activation of lymphocytes. The activated T lymphocytes can then differentiate into effector T cells that fight infections or into memory T cells that ensure a faster response to future infections by the same pathogen. Dendritic cells reside in the skin, lymph nodes, and tissues throughout the body. They are specialized in the presentation of antigens with intense activity in the lymph nodes, small lymph nodes that work as filters for harmful substances. In addition, dendritic cells release cytokines, which are molecules that signal proliferation and differentiation of T and B lymphocytes. Cytokines secreted by CD not only help promote lymphocyte activation, but also play a role in regulating the immune response, helping to balance the inflammatory response and immune tolerance. In summary, CD are essential for the orchestration of the adaptive immune response that takes time to develop after the first exposure to a new antigen, thus acting as mediators between the innate and adaptive response, facilitating the activation of lymphocytes and ensuring a highly specific immune response, with memory, and, consequently, quite effective.